Molecular phylogeny and diversification history of Prosopis (Fabaceae: Mimosoideae) - Catalano, Santiago Andres (2008)
The genus Prosopis is an important member of arid and semiarid environments around the world. To study Prosopis diversification and evolution, a combined approach including molecular phylogeny, molecular dating, and character optimization analysis was applied. Phylogenetic relationships were inferred from five different molecular markers (matK-trnK, trnL-trnF, trnS-psbC, G3pdh, NIA). Taxon sampling involved a total of 30 Prosopis species that represented all Sections and Series and the complete geographical range of the genus. The results suggest that Prosopis is not a natural group. Molecular dating analysis indicates that the divergence between Section Strombocarpa and Section Algarobia plus Section Monilicarpa occurred in the Oligocene, contrasting with a much recent diversification (Late Miocene) within each of these groups. The diversification of the group formed by species of Series Chilenses, Pallidae, and Ruscifoliae is inferred to have started in the Pliocene, showing a high diversification rate. The moment of diversification within the major lineages of American species of Prosopis is coincident with the spreading of arid areas in the Americas, suggesting a climatic control for diversification of the group. Optimization of habitat parameters suggests an ancient occupation of arid environments by Prosopis species.